2023
DOI: 10.2147/amep.s381139
|View full text |Cite
|
Sign up to set email alerts
|

“We Need More Practice”: Evaluating the Role of Virtual Mock OSCES in the Undergraduate Programme During the COVID Pandemic

Abstract: Background Feedback collated at University College London Medical School (UCLMS) during the COVID pandemic identified how many students felt unprepared for their summative Objective Structured Clinical Examinations (OSCEs) despite attending mock face-to-face OSCEs. The aim of this study was to explore the role of virtual mock OSCES for improving student’s sense of preparedness and confidence levels for their summative OSCEs. Methods All Year 5 students (n=354) were elig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Aligned with other studies, our results showed that clinical skills which are best learned in clinics and laboratories remain a pertinent barrier to online teaching. 2,18,25,40,[43][44][45] Similarly to other studies, the most enjoyable aspects of online learning appeared to be the online accessibility of materials, flexibility of the time, ability to learn at own pace and cost saving. 2,42 Post pandemic recommendations suggested to maintain flexibility and accessibility to educational resources.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Aligned with other studies, our results showed that clinical skills which are best learned in clinics and laboratories remain a pertinent barrier to online teaching. 2,18,25,40,[43][44][45] Similarly to other studies, the most enjoyable aspects of online learning appeared to be the online accessibility of materials, flexibility of the time, ability to learn at own pace and cost saving. 2,42 Post pandemic recommendations suggested to maintain flexibility and accessibility to educational resources.…”
Section: Discussionmentioning
confidence: 56%
“…However, this role was not reflected in their confidence levels. 18 Nevertheless, some potential benefits of online technologies are reported including easy and comfortable use, worldwide acceptability besides the reductions in cost and air pollution due to less need for transportation. 2,7,[19][20][21][22] On the other hand, significant issues have been pointed out about the use of entirely online education such as: physical and social isolation, increased use of emails, difficulty to keep boundaries between time at the workplace and at home, lack of interaction, disturbance and technical problems, deficiency in integrated teaching and bed-side teaching, inadequate teaching and learning in practical and clinical settings besides time constraints for effective implementation of online education.…”
Section: Introductionmentioning
confidence: 99%
“…Lim et al assessed whether virtual mock OSCEs improved students’ self-reported sense of preparedness and confidence for their summative OSCEs, and concluded that although students felt there was not a significant improvement in their confidence levels, they gained a greater sense of preparedness. 1 However, we found that the authors have not adequately replicated summative exam conditions, nor have they holistically assessed the effect on the students of virtual mock OSCEs.…”
Section: Dear Editormentioning
confidence: 80%
“…We read, with interest, the study by Lim et al exploring the role of virtual mock Objective Structured Clinical Examinations (OSCEs) during a global pandemic. 1 As medical students we have experienced first-hand the difficulty of translating in-person teaching to an online medium, and greatly appreciate the time and effort undertaken by the authors to improve the quality of OSCE practice for students.…”
Section: Dear Editormentioning
confidence: 99%
See 1 more Smart Citation